Legal Reform in Village Law-Making Process Using Artificial Intelligence: Is It Necessary? - Sholahuddin Al-Fatih; Ali Roziqin; Muhammad Dahlan Asyari; Souad Ezzerouali (Journal of Law and Legal Reform, 2025)
This article aims to discuss how Village Regulation should be implemented in the digital age, whether using artificial intelligence or conventional methods. Indonesia is a big country with too many villages, such as the small Regency/City of Malang, which has almost 390 villages (with different terms, both desa and kelurahan). The problem was raised while those villages were drafting Village Regulation. By using a legal research method, this research examines how AI could help in the village law-making process. To do that, this article combines both normative and empirical studies by analyzing the norms and literature, as well as understanding the respondent answers spread out by Google Forms. As a result, this paper finds that some AIs are necessary for drafting village regulations, such as ChatGPT, Gemini, Scopus AI, and so on. However, those AI should be used responsibly, with an honest principle, an open mind, and the avoidance of plagiarism.